The two-component system CpxAR is required for the high potassium stress survival of Actinobacillus pleuropneumoniae - Wan, Jiajia; Zhang, Rui; Jia, Yizhen; Xie, Tingting; Dai, Lu; Yao, Qing; Zhang, Wendie; Xiao, Huasong; Gao, Xuejun; Huang, Jing; Bei, Weicheng; Liu, Feng (Frontiers in Microbiology, 2023)
Actinobacillus pleuropneumoniae is an important respiratory pathogen, which can cause porcine contagious pleuropneumonia and lead to great economic losses to worldwide swine industry. High potassium is an adverse environment for bacteria, which is not conducive to providing turgor pressure for cell growth and division. Two-component system CpxAR is an important regulatory system of bacteria in response to environmental changes, which is involved in a variety of biological activities, such as antibiotic resistance, periplasmic protein folding, peptidoglycan metabolism and so on. However, little is known about the role of CpxAR in high potassium stress in A. pleuropneumoniae. Here, we showed that CpxAR is critical for cell division of A. pleuropneumoniae under high potassium (K + ) stress. qRT-PCR analysis found that CpxAR positively regulated the cell division genes ftsEX. In addition, we also demonstrated that CpxR-P could directly bind the promoter region of the cell division gene ftsE by EMSA. In conclusion, our results described a mechanism where CpxAR adjusts A. pleuropneumoniae survival under high-K + stress by upregulating the expression of the cell division proteins FtsE and FtsX. These findings are the first to directly demonstrate CpxAR-mediated high-K + tolerance, and to investigate the detailed molecular mechanism.